The closely related transcription factors Sox4 and Sox11 function as survival factors during spinal cord development. - Hartwig, Anna; Wegner, Michael; Sock, Elisabeth; et al. (Journal of neurochemistry, 2010)
Development of the mouse CNS was reported to be normal in the absence of either Sox4 or its close relative Sox11 despite strong and widespread expression of both transcription factors. In this study, we show that combined absence of both Sox proteins in the mouse leads to severe hypoplasia of the developing spinal cord. Proliferation of neuroepithelial precursor cells in the ventricular zone was unaffected. These cells also acquired their correct positional identity. Both glial and neuronal progenitors were generated and neurons appeared in a similar spatiotemporal pattern as in the wild-type. Rates of cell death were however dramatically increased throughout embryogenesis in the double deficient spinal cord arguing that Sox4 and Sox11 are jointly and redundantly required for cell survival. The absence of pronounced proliferation, patterning, specification, and maturation defects furthermore indicates that the decreased cell survival is not a secondary effect of one of these events. We therefore conclude that the two Sox proteins directly function as pro-survival factors during spinal cord development in neural cell types. © 2010 International Society for Neurochemistry.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.theclo
Keywords: apoptosis; cell survival; gliogenesis; neurogenesis; proliferation; spinal cord